Baicalein Induces Apoptosis and Autophagy via Endoplasmic Reticulum Stress in Hepatocellular Carcinoma Cells. (3rd June 2014) - Wang, Zhongxia; Jiang, Chunping; Chen, Weibo; Zhang, Guang; Luo, Dongjun; Cao, Yin; Wu, Junhua; Ding, Yitao; Liu, Baorui
Abstract : Background . Hepatocellular carcinoma (HCC) remains a disastrous disease and the treatment for HCC is rather limited. Separation and identification of active compounds from traditionally used herbs in HCC treatment may shed light on novel therapeutic drugs for HCC. Methods . Cell viability and colony forming assay were conducted to determine anti-HCC activity. Morphology of cells and activity of caspases were analyzed. Antiapoptotic Bcl-2 family proteins and JNK were also examined. Levels of unfolded protein response (UPR) markers were determined and intracellular calcium was assayed. Small interfering RNAs (siRNAs) were used to investigate the role of UPR and autophagy in baicalein-induced cell death. Results . Among four studied flavonoids, only baicalein exhibited satisfactory inhibition of viability and colony formation of HCC cells within water-soluble concentration. Baicalein induced apoptosis via endoplasmic reticulum (ER) stress, possibly by downregulating prosurvival Bcl-2 family, increasing intracellular calcium, and activating JNK. CHOP was the executor of cell death during baicalein-induced ER stress while eIF2 α and IRE1 α played protective roles. Protective autophagy was also triggered by baicalein in HCC cells. Conclusion . Baicalein exhibits prominent anti-HCC activity. This flavonoid induces apoptosis and protective autophagy via ER stress. Combination of baicalein and autophagy inhibitors may represent a promising therapy against HCC.